Supplementary dataset to: "Optimization of monitoring indicators for gastrointestinal parasite resistance in Corriedale sheep” [Conjunto de datos] - Cordoba, Marcela Elisabet; Raschia, Maria Agustina; Donzelli, María Valeria; Cetra, Bibiana Maria; Medus, Pablo Daniel; Bonelli, Rita; Poli, Mario Andres; Maizon, Daniel Omar (INTA, 2025)
The dataset consists of estimated breeding values (EBV) for fecal egg counts from 939 Corriedale lambs experimentally challenged with Haemonchus contortus infective larvae. During the challenge period, measures of FEC were taken at 28, 35, and 42 days post-infection. FEC values were transformed using the function ln(FEC+250) (lnFEC) to approximate normality. Averages of lnFEC were calculated for 28 and 35 days (lnFEC2835), 35 and 42 days (lnFEC3542), and from 28 to 42 days (lnFEC2842). Individual measurements for each day (28, 35, and 42) were also analyzed (lnFEC28, lnFEC35, and lnFEC42, respectively). Univariate mixed models for partial (lnFEC2835, lnFEC3542), single (lnFEC28, lnFEC35, and lnFEC42), and complete (lnFEC2842) records were fitted using BLUPF90+ and individual breeding values were estimated. Subsequently, Kendall’s Tau-b, Spearman correlations, and Concordance Correlation Coefficients between EBVs obtained with traits based on using partial records (lnFEC2835 and lnFEC3542) or single records (lnFEC28, lnFEC35, and lnFEC42) and the EBVs for the whole information collected (lnFEC2842) were calculated. We are uploading a file with the EBVs used for the study, in which columns 1, 2, 3, 4, 5, and 6 indicate the EBVs based on lnFEC2842, lnFEC2835, lnFEC3542, lnFEC28, lnFEC35, and lnFEC42 records, respectively.